2024
DOI: 10.1097/md.0000000000037029
|View full text |Cite
|
Sign up to set email alerts
|

Acupoint herbal patching for postherpetic neuralgia: A systematic review and meta-analysis

Bingyu Pu,
Xiaoxue Lu,
Peilin Yu
et al.

Abstract: Background: This study aimed to systematically evaluate the clinical effectiveness and safety of acupoint herbal patching in the treatment of postherpetic neuralgia. Methods: Eight databases including PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wan-Fang Database, China Biomedical Literature Service System, and Chongqing VIP Chinese Science were searched. The search time was set to October 2023. Two research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…A systematic review and meta-analysis of randomized controlled trials (RCTs) have demonstrated the efficacy of acupuncture and moxibustion in reducing pain intensity in patients with PHN. 12,13 Moreover, moxibustion has been reported to have fewer side effects compared to pharmacological interventions, making it an attractive option for patients who are unable to tolerate the side effects of conventional pain medications or who are seeking a non-pharmacological approach to pain management. 13 Bibliometrics is the field that involves the measurement and statistical analysis of scientific publications, reports, books, and other…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis of randomized controlled trials (RCTs) have demonstrated the efficacy of acupuncture and moxibustion in reducing pain intensity in patients with PHN. 12,13 Moreover, moxibustion has been reported to have fewer side effects compared to pharmacological interventions, making it an attractive option for patients who are unable to tolerate the side effects of conventional pain medications or who are seeking a non-pharmacological approach to pain management. 13 Bibliometrics is the field that involves the measurement and statistical analysis of scientific publications, reports, books, and other…”
Section: Introductionmentioning
confidence: 99%